A new species of Polyodaspis Duda, 1933 (Diptera: Chloropidae) from Romania with list of Chloropidae, collected in the country - E.P. Nartshuk (Кавказский энтомологический бюллетень, 2014)
Results of identification of Chloropidae (Diptera) from Romania, deposited in the Natural History Museum (London, UK) is presented. Collection contains 24 species from 16 genera. A species Polyodaspis maritima Nartshuk, sp. n. is described as new and 5 species Calamoncosis aprica (Meigen, 1830), Calamoncosis duinensis (Strobl, 1909), Aphanotrigonum inerme Collin, 1946, Conioscinella gallarum (Duda, 1932) and Chlorops meigenii Loew, 1866 are recorded for the first time for the fauna of Romania